Siltuximab-Related Favorable Clinical Outcome for a Patient Suffering from Idiopathic Multicentric Castleman Disease - Stamatios Chrysochoou; Andreas Kreft; Eberhard Schneider (Case Reports in Hematology)
RationalCastleman disease is a rare lymphoproliferative disorder that can be subdivided into unicentric and multicentric forms, the latter of which causes a spectrum of serious medical conditions. Here, we present a case of idiopathic multicentric Castleman disease in the eighth decade of life. Patient Concerns. First hospitalized due to unexplained progressive anemia, the patient was readmitted to the hospital 18 months later with suspected lymphoma. Clinical examination revealed a progressive lymphadenopathy. Diagnoses. Histopathologic lymph node features, anemia, elevated CRP and IL6 levels, splenomegaly, and hypoalbuminemia indicated multicentric Castleman (MCD) disease. Interventions. The patient was treated intravenously with a dose of 11 mg/kg siltuximab every 3 weeks. Outcomes. Timely correct diagnosis through the stringent use of consensus diagnostic criteria and sufficient siltuximab therapy has considerably promoted favorable clinical outcomes in a patient suffering from MCD.